How can smart mobility bridge the first/last mile gap? Empirical evidence on public attitudes from Australia. (October 2022) - Butler, Luke; Yigitcanlar, Tan; Paz, Alexander; Areed, Wala
Abstract: Under the umbrella concept of smart mobility, new transport innovations such as peer-to-peer transport, shared autonomous vehicles, and mobility-as-a-service have been identified for their potential to improve accessibility and bridge the first/last-mile gap between origin, destination, and good quality public transport. Any future mobility plan, nevertheless, will need to appeal to a population reluctant to break habits. This study explores quantitative data collected from major Australian cities to provide a geographic context between attitudes towards smart mobility with a particular focus on eight attitudinal factors—i.e., technology, public transport, sharing, multimodality, peer-to-peer transport, smart phones and apps, environmental consciousness, and reducing private vehicle use. The quantitative analysis disclosed that regardless of location, overcoming private vehicle use, user aversion to multimodality, and reluctance to share rides with strangers' presence significant barriers to some smart mobility options. Furthermore, respondents in inner ring areas of cities have more positive views towards public transport, the environment, and smart phones, while the middle/outer ring residents on the contrary have more positive views towards private vehicles. The study findings offer policy insights and potential opportunities and challenges associated with the implementation of smart mobility in urban areas. Highlights: Explores factors affecting user attitudes towards smart mobility. Identifies the key attitudinal factors related to implementation of smart mobility. Provides insights into user attitudes regarding smart mobility. Emphasises opportunities and barriers to implement in urban areas. Offers insights for future planning and policy direction related to smart mobility adoption.